Ognozja, czyli Olgi Tokarczuk teologia sekularna = Ognosia, or Olga Tokarczuk`s secular theology - Draguła, Andrzej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Olga Tokarczuk proposes - both in the Nobel Prize lecture and in her essays - her concept of literature, the features of which are the project she calls ognosia, based on a four-person (panoptical) narrator, or the understanding and function of myth, and more broadly - of all narration. As she believes, her concept can be considered as alter-religious. She refers to the nature of the biblical narrative to - resorting to analogy - describe her view of an author and other components of a literary work.
Keywords: Tokarczuk, Olga (1962- ); Northrop Frye; literatura; mit; Biblia; literature; Bible; myth